The Islamization of Economic Systems: A Methodological Approach - Mi'raj, Denizar Abdurrahman; Yatoo, Nissar Ahmad (al-Uqud : Journal of Islamic Economics, 2020)
This paper is an attempt to discuss Islamization of economics in historical perspective. Focus of the discussion is not only the Islamization of economics but also realization of an Islamic economic system. This research is based on library research methods and supported by historical analysis. Conclusive information was collected from various studies and analysed for the conception of implementing methodological steps to realize the Islamization of the economic system. Studies were reviewed and investigated in three stages: general, exploratory, and focused learning. The findings of this study reveal that Islamization of economics cannot stand alone without the Islamization of every Muslim and the Islamization of society. Like Islamization of a society is realized with organization of Muslim families, Islamization of economics can be realized by increasing the number of economists who have knowledge of sharia.